1999
DOI: 10.1088/0952-4746/19/3/304
|View full text |Cite
|
Sign up to set email alerts
|

Strategy for population protection and area rehabilitation in Russia in the remote period after the Chernobyl accident

Abstract: The report presents the history of the development of criteria for radiation and social protection of the Russian population residing in the areas contaminated with radionuclides after the Chernobyl accident, in the remote time periods after the accident. The tendencies for reduction of standards with time are shown, and their causes are analysed. It is noted that the optimization principle was not applied in the explicit form for population protection. The current radiation situation in the contaminated areas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…In 1991-1998 the contribution from E int to E tot , was between 17 and 75%, depending on the village, see Table 2. The average contributions from E int and E ext to E tot are expected to be proportionally equal in this area between 2000 and 2056, for people not consuming forest products, while E int could be expected to be a factor of 1.5-3 times higher than E ext for people consuming significant amounts of these products (33).…”
Section: Temporal Trends and The Annual Effective Dose From Internal mentioning
confidence: 96%
“…In 1991-1998 the contribution from E int to E tot , was between 17 and 75%, depending on the village, see Table 2. The average contributions from E int and E ext to E tot are expected to be proportionally equal in this area between 2000 and 2056, for people not consuming forest products, while E int could be expected to be a factor of 1.5-3 times higher than E ext for people consuming significant amounts of these products (33).…”
Section: Temporal Trends and The Annual Effective Dose From Internal mentioning
confidence: 96%
“…In heavily contaminated parts of Sweden in the period of 1987e1995, migration rates for the Chernobyl radiocesium ranged from 0.2 to 0.6 cm y ÿ1 (Rosen et al, 1999), depending, again, on soil types. One should bear in mind, however, that many other factors such as mechanical mixing of the upper soil layer by grazing cattle, porosity and cracks of the topsoil layer, immobilization of Cs by soil microflora, accumulation of the radionuclides in fungi, etc., may influence the rates of migration as well Barisic et al, 1999). It was evident that on intensively exploited grassy plots (which were called yards) located inside the settlements, and on cultivated lands, mechanical migration of radiocesium with the soil particles played the leading role in the redistribution of the contaminant.…”
Section: Distributions Of 137 Cs and 134 Cs In Soil Coresmentioning
confidence: 99%
“…This paper deals with the doses from external gamma radiation, which in rural areas may contribute up to 50% and more of the total accidental dose Balonov et al, 1999;Radiation and Risk, 1999). It was demonstrated that the average annual external doses varied markedly among different social and professional groups (Jacob and Likhtarev, 1996;Golikov et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…However, wild-forest products, such as berries, mushrooms, and animal meat, contain considerable amounts of 137 Cs, up to 100 times higher concentration of cesium than local and home-grown meat. They contribute considerably (10-70%) to the internal effective dose [21,22]. In the domain of internal exposure, intake habits of individuals and the type of food consumed in the affected areas are the most important factors determining the level of internal exposure.…”
Section: Plos Onementioning
confidence: 99%
“…These products include highly 137 Cs contaminated mushrooms, forest berries, wild animal meat, and fish [3,26]. Another major factor is the abundance of forest food (mushrooms, berries, games), which can have up to 100 times higher concentrations of cesium than local milk and meat and hence contributes considerably (10-70%) to the internal effective dose [21,22]. In a study by Bernhardsson in 1998, the internal exposure of participants was four times higher than that in the preceding year, presumably owing to abundance [19].…”
Section: Plos Onementioning
confidence: 99%